Circular RNA–based therapy targeting metabolic vulnerability of fatty acid synthesis overcomes castration-resistant prostate cancer - Yudong Lin; Ruyue Wang; Fan Li; Zeyi Lu; Wenqin Luo; Haohua Lu; Zhehao Xu; Chang Xu; Yi Lu; Ziwei Zhu; Yang Li; Xudong Mao; et al. (Proceedings of the National Academy of Sciences, 2026)
Androgen receptor (AR) signaling is essential for prostate cancer (PCa) cell growth and remains a key therapeutic target in castration-resistant PCa (CRPC). While circular RNAs (circRNAs) are increasingly recognized as important regulatory molecules, their roles in AR signaling during PCa progression remain poorly understood. This study identified circUTRN , an AR-inhibited circRNA that is upregulated following neoadjuvant hormonal therapy and downregulated in PCa tissues. circUTRN inhibits proliferation in both castration-sensitive and castration-resistant PCa. Mechanistically, circUTRN binds to acetyl-CoA carboxylase 1 (ACC1) and impairs the activity through both phosphorylation-dependent and independent pathways, thereby disturbing de novo fatty acid synthesis. The dynamic relation between circUTRN and ACC1 expression during PCa progression from treatment-naïve to therapeutic-resistant states highlights the metabolic vulnerability of fatty acid synthesis. Notably, we developed nanoparticles to deliver circUTRN in combination with AR signaling inhibitors (ARSIs). This approach effectively suppressed CRPC xenograft tumor growth, even in models resistant to next-generation ARSIs. This study reveals an AR-regulated circRNA involved in PCa progression and suggests a potential therapeutic strategy for treatment-resistant PCa.